Comparative Estimation of Ascorbic Acid in Healthy and Rust Infected Aonla (Phyllanthus emblica L.) Fruits: Insights into Plant Resistance Mechanisms - Shubham Patel; Hemant Kumar Singh; Vivek Singh; Virendra Prasad Chaudhary; Jitendra Kumar (The Bioscan, 2025)
Aonla (Phyllanthus emblica Linn.), revered for its exceptional nutraceutical properties and therapeutic value, is a significant fruit crop in India and other tropical regions. Despite its hardiness, the crop is vulnerable to rust disease caused by Phakopsora phyllanthi, which adversely affects both yield and post-harvest quality. This study aimed to evaluate the biochemical response specifically Vitamin C (ascorbic acid) content of thirteen aonla cultivars under healthy and rust-infected conditions over two developmental stages (60 and 90 days after infection). Vitamin C content consistently declined under infected conditions, with NA-25, NA-26, and BSR-1 maintaining significantly higher levels compared to other genotypes, highlighting their superior nutritional retention and potential disease resilience. Principal Component Analysis (PCA) revealed that the first component accounted for 95.72% of the variance, confirming its dominant influence. The PCA biplot analysis further illustrated strong associations between rust infection and biochemical degradation, particularly distinguishing between healthy and infected states via PC2. These findings underscore the importance of genotype-dependent variability in disease tolerance and offer valuable insight for breeding disease-resistant, nutritionally superior aonla cultivars.